Disrupsi Pembelajaran dan Kesiapan Sekolah: Studi Perbandingan Sebelum dan Setelah Pandemi Covid-19 - Desvianti, Erika; Rahmi, Iftita (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
​ The COVID-19 pandemic has had a significant impact on educational systems worldwide, leading to widespread school closures and disruptions to early childhood education. This situation has affected the readiness of young children to progress to higher levels of education (elementary school). This study aims to examine differences in school readiness between kindergarten student groups before and during the pandemic. A comparative study design was used, assessing 36 kindergarten students, with 10 students from each group, using the Nijmeegse Schoolbekwaamheids Test (NST). The NST consists of 10 subtests measuring various aspects of school readiness, including cognitive, social-emotional, and physical developmental skills. Statistical analyses were conducted to compare school readiness profiles between the two groups. The results showed no statistically significant differences between the pre-pandemic and post-pandemic groups in terms of overall school readiness. However, univariate analysis indicated significant differences in Subtest 3 (understanding of size, quantity, and comparison) and Subtest 4 (accuracy and detail in visual perception), where the pre-pandemic group performed better than the post-pandemic group. The effect sizes for these subtests were considerable, indicating meaningful practical differences in these two abilities. These findings highlight the impact of educational disruptions on certain aspects of school readiness and underscore the need for targeted interventions to mitigate the negative effects of the pandemic on early childhood education, especially regarding quantitative reasoning and visual perception skills.